Large‐Scale Synthesis of Helicene‐Like Molecules for the Design of Enantiopure Thin Films with Strong Chiroptical Activity. Issue 10 (21st January 2016) - Bensalah‐Ledoux, Amina; Pitrat, Delphine; Reynaldo, Thibault; Srebro‐Hooper, Monika; Moore, Barry; Autschbach, Jochen; Crassous, Jeanne; Guy, Stéphan; Guy, Laure
Abstract: Helicenes are fascinating molecules owing to their unusual properties and applications in many fields from catalysis to organic electronics. Herein, we report a straightforward pathway for the synthesis of helicene‐like molecules on a gram scale in an enantiopure form. Thin‐film materials with good propagating optical properties and very high chiroptical responses have been grown by using pulsed laser ablation without altering the structure or the enantiopurity of the molecules. Moreover, electronic and vibrational circular dichroism spectroscopies coupled with theoretical calculations enabled some dependences of the chiroptical properties with the structure to be highlighted, for example, effects of rigidification, aromatization, or the state of matter (liquid versus solid). Abstract : From molecule to material : A straightforward pathway for the synthesis of helicene‐like molecules on a gram scale in an enantiopure form allowed the fabrication of thin‐film materials with good propagating optical properties. Their very high chiroptical responses have been investigated by electronic and vibrational circular dichroism spectroscopy coupled with theoretical calculations.